Early education: exploration of objects as a learning experiencie (Olhar de Professor, 2020)
Exploration is one of the usual forms of pedagogical activity in the kindergarten. In this paper, theidea of exploration is deepened, from a sensitive approach to space, objects, body and relationships. To exploreis to ask, to ask oneself with the gesture and the senses, to question the object. In turn, we differentiate betweenthe concepts of floor and ground, flat ceiling and frieze ceiling. Some assumptions are also reviewed from aninterdisciplinary point of view (between psychomotricity and pedagogy) and images and metaphors are proposedto think about this way of approaching the experience of babies in the maternal, giving to explore.
Keywords: Early Childhood. Child Care And Education. Psychomotricity. Explore.